Clinical and Biochemical Associations with Diabetic Retinopathy in Male Patients in the Gaza Strip - AbuMustafa, Ayman M. (Frontiers in Endocrinology, 2017)
Background: There are limited data on the prevalence and risk factors for diabetic retinopathy (DR) in the Gaza Strip. Objective: To assesses clinical and biochemical associated with diabetic retinopathy in males with type 2 diabetes mellitus (T2DM) in the Gaza Strip. Methods: 150 males with T2DM from the Gaza Strip underwent a questionnaire interview, serum biochemical analysis and assessment of their previous urine and blood results. Results: The prevalence of diabetic retinopathy was 24.7%. The duration of diabetes and prevalence of neuropathy, nephropathy, cardiovascular disease (CVD) and recurrent infections was significantly higher among patients with DR compared to those without DR (p<0.05). Serum urea, creatinine, glucose, cholesterol and LDL-C were significantly elevated, whilst eGFR and HDL-C were significantly lower in patients with DR compared to patients without DR (p<0.05). Urinary albumin concentration and albumin creatinine ratio (ACR) was higher in patients with DR. ACR correlated significantly with the duration of T2DM (r=0.311, p<0.001), glucose (r=0.479, p<0.001), urea (r=0.337, p<0.001), creatinine (r=0.275, p=0.001) and GFR (r=-0.275, p<0.001). Conclusion: These data show a high prevalence of DR in an unselected cohort of patients with T2DM and relationships to modifiable risk factors in Gaza. Keywords: Diabetic Retinopathy, Biochemical, Clinical, Male, Gaza Strip.